A Diet Containing Beta-Hydroxy-Beta-Methylbutyrate, L-Glutamine and L-Arginine Ameliorates Chemoradiation-Induced Gastrointestinal Injury in Rats - (:unkn) unknown (RADIATION RESEARCH SOC, 2015)
The aim of this study was to investigate the effects of a specific diet, containing beta-hydroxy-beta-methylbutyrate, L-glutamine and L-arginine (HMB/Glu/Arg), on chemoradiation-induced injuries of the rat gastrointestinal mucosa. Wistar albino rats were divided into 4 groups: control (n = 5); radiation (n = 14); 5-fluorouracil treatment (5-FU; n = 14); and radiation and 5-FU treatment (n = 14). Rats were fed either a standard diet or a specific diet (SpD) containing HMB/Glu/Arg supplementation for 7 days prior to radiation exposure and/or 5-FU treatment. The irradiated groups were exposed to an 1 Gy dose of 6 MV x rays delivered to the who-abdominal. The animals receiving 5-FU treatment were given a 100 mg/kg dose of the drug. In the radiation and 5FU treatment group, the 5-FU was administered 30 min prior to irradiation. After irradiation and/or 5-FU treatment, feeding with either the standard rat diet or specific diet continued as before. All animals were sacrificed on day 4 after irradiation and 5-FU treatment. Data collected included microbiological, histological and immunohistochemical end points. We found that bacterial colony counts in the ceca and mesenteric lymph nodes of irradiated rats treated with 5-FU were significantly lower in the specific diet (SpD) group than in the standard diet group (P = 0.002-0.05). Morphometrically, gastric, duodenal and colonic mucosal injuries were less severe in the irradiated animals fed the specific diet, as well as the 5-FU-treated animals fed the specific diet, compared to the similarly treated standard diet groups. Apoptosis, measured by TUNEL, revealed significantly lower numbers of TUNEL positive cells in irradiated animals fed the specific diet, and irradiated animals treated with 5-FU and fed the specific diet compared to irradiated animals fed the standard diet, and irradiated animals treated with 5-FU and fed the standard diet. In the 5-Fu-treated and SpD group, the extent of apoptosis was significantly lower than that of the 5-Futreated and standard diet group in both the stomach and duodenum (P = 0.0001), but not in the colon. Apoptosis, measured by caspase 3 staining, was significantly less in all three organs of the SpD groups. In conclusion, these findings suggest that a diet supplemented with HMB/Glu/Arg may ameliorate the effect of radiation-induced gastrointestinal injury, coinciding with reduced bacterial growth. (C) 2015 by Radiation Research Society
Keywords: PELVIC RADIOTHERAPY; DOUBLE-BLIND; NUTRITIONAL INTERVENTION; BACTERIAL TRANSLOCATION; IMMUNE-RESPONSES; GUT MICROFLORA; CANCER; SUPPLEMENTATION; COMPLICATIONS; CACHEXIA